IMPLEMENTATION OF SPECIAL CHILD SERVICE ROOMS IN THE INVESTIGATION OF CHILDREN IN CONFLICT WITH THE LAW - Tamba, Randi Pandapotan; DM, M. Yusuf; Andrizal (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The purpose of this study is to analyze the implementation of the Special Service Room for Children in the Investigation of Children in Conflict with the Law at the Rokan Hilir Police, to analyze the obstacles to the implementation of the Special Service Room for Children in the Investigation of Children in Conflict with the Law at the Rokan Hilir Police, and to analyze efforts to overcome obstacles in the implementation of the Special Service Room for Children in the Investigation of Children in Conflict with the Law at the Rokan Hilir Police. The method used is sociological legal research. Based on the results of the study, it is known that the Implementation of the Special Service Room for Children in the Investigation of Children in Conflict with the Law at the Rokan Hilir Police that the special service room for children at the Rokan Hilir Police has not run as it should be mandated by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, this is because there is no special service room for children in the investigation of children in conflict with the law. This room is not only a place for examination, but also a place for protection and psychological recovery for children. Obstacles are budget limitations and physical infrastructure limitations, lack of competent human resources, weak coordination between institutions, and the lack of collective awareness of the community about the importance of a just legal approach to children.